Applications, Benefits, and Risks of ChatGPT in Medical and Health Sciences Research: An Experimental Study - Al-Worafi, Yaser Mohammed; Hermansyah, Andi; Tan, Ching Siang; Choo, Chee Yan; Bouyahya, Abdelhakim; Ganesh, Sritheran Paneerselvam; Liew, Kai Bin; Goh, Khang Wen; Long, Chiau Ming * (HH Publisher, 2023)
This article explored the potential applications, benefits, and risks of using ChatGPT in medical and health sciences research. The experimental study was performed with content analysis of the potential applications, benefits and risks of using ChatGPT in medical and health sciences research. This study shows many potential applications, benefits, and risks of using ChatGPT in medical and health sciences research. The average experts’ ChatGPT appropriateness and accuracy rates in the eight research themes were between 60% and 95%. This concludes that ChatGPT could help medical and health sciences researchers, especially new researchers, with caution in many aspects of research. The ChatGPT is still in the early phase of use by researchers worldwide, and its ability to help in research will be better soon. Attending training workshops about ChatGPT and AI is very important and highly recommended. The practice of ChatGPT in medical and health sciences research is important and recommended to explore the potential uses, benefits, risks and suggest recommendations for the best practice.